Students’ Models of Magnetic Interactions: A Comparative Analysis of Accurate and Inaccurate Models over a Ten-Year Interval - Yuksel, Tugba; Bryan, Lynn A. (Science Insights Education Frontiers, 2023)
This research investigates the Models of eighth-grade students in Turkey pertaining to magnets and magnetic interactions, while also examining the consistency of these models within themselves. Additionally, a comparative assessment is conducted by comparing the current data with data collected from eighth-grade students a decade earlier. The study comprises 59 students in the first phase and 45 students in the second phase, all of whom briefly received formal instruction on magnetism during fourth grade. The focus of the analysis centers on identifying the students’ Models and evaluating their coherence across diverse contexts in both phases. Surprisingly, despite the passage of ten years, the mental model patterns exhibited by the students in both studies remain remarkably similar. Three primary categories emerged from the students’ Models of magnets, including attraction and repulsion, magnetic poles, and the composition and functionality of magnets. However, noticeable distinctions between the two studies are evident. In the earlier study, the students’ responses to survey questions displayed a greater variety and detail in comparison to the responses from the later study. Moreover, the second study revealed fewer instances of inconsistent Models concerning the magnetic interaction between magnets and nails, but more instances of inaccurate Models compared to the first study. The findings of this investigation offer valuable insights to educators, guiding them in designing effective lessons and activities aimed at helping students overcome their inaccurate and inconsistent Models.